Research on the Application of Chaozhou Gold Lacquered Wood Carving 'Shrimp and Crab Basket' in Traditional Architectural Design - Ye, Jing; Zhang, Chen (Transactions on Social Science, Education and Humanities Research, 2024)
Chaozhou gold lacquered wood carving, as an outstanding representative of traditional Chinese crafts, holds a unique position in the field of traditional Chinese architectural art due to its exquisite craftsmanship and profound cultural heritage. This paper focuses on the 'Shrimp and Crab Basket' element, showcasing its significant achievements at both technical and cultural levels. Through in-depth literature research and investigation of lacquer craftsmanship, this study explores the historical background and craft characteristics of Chaozhou gold lacquered wood carving, with a particular emphasis on the importance of the 'Shrimp and Crab Basket' in this tradition. The paper also examines the unique features of Chaozhou traditional architectural decorative art, providing a rich context for understanding the application of the 'Shrimp and Crab Basket' in the field of architecture. It specifically analyzes examples of the 'Shrimp and Crab Basket' in various traditional Chaozhou buildings, revealing its functional and symbolic significance in architectural design and discussing how to innovate artistically while respecting tradition. Ultimately, the paper summarizes the important role of the 'Shrimp and Crab Basket' in traditional Chaozhou architectural design and looks forward to its potential applications in future architectural design. This research not only deepens the understanding of Chaozhou gold lacquered wood carving art but also offers a new perspective on the application of traditional crafts in modern architectural design.